CHARACTERISTICS AND MODERN PROBLEMS OF TRANSPORTATION OF DANGEROUS CARGOES IN RUSSIA - A. Ochkalova (Вестник университета)
The article describes the definition of dangerous goods, analyze the market of potential producers of dangerous goods is presented, growth forecasts for these products is given, the requirements for the organization of transportation of dangerous goods according to the European Agreement concerning the International Carriage of Dangerous Goods by Road are considered, the complexity of high-risk cargoes is given, the problem of a shortage of specialized transportation in Russia is announced.